Accessibility of Hotels for People with Visual Impairments: From Research to Practice. (May 2016) - Tutuncu, Ozkan; Lieberman, Lauren
Introduction: Standards are available to guide tourism facilities in providing barrier-free environments for the independence, convenience, and safety of people with disabilities. These standards can be especially beneficial to individuals who face many barriers in daily life and tourism activities, such as those with visual impairments. On the other hand, some barriers faced by individuals with visual impairments in this arena are specific and may not be improved by only these regulations. Purpose: The purpose of this study was to find the main barriers in hotels and evaluate the accessibility of hotels for people with visual impairments. Methods: Qualitative research methods were used to explore determinants of barriers to the accessibility of tourism facilities for people with visual impairments. Semi-structured, open-ended questions were distributed to individuals with visual impairments. Results: Sixty-six participants with visual impairments shared their experiences with hotels. Themes that emerged from the data were categorized into three settings: entrance, guest rooms, and other hotel settings. People with visual impairments discussed all hotel settings with regard to signage; braille; lighting, color, and contrast; and layout. Discussion: Those with visual impairments expressed needs that related specifically to their own disabilities. Their problems are clear and can be solved if hotel managers focus on their needs. Standards and checklists can be helpful to solve many problems, but they are not meaningful without real audits. The needs of people with visual impairments do not require considerable investments but rather a transformation in existing attitudes and policies. Implications for practitioners: From the findings, an accessibility checklist was developed for hotel managers to address barriers for people with visual impairments.